2020
DOI: 10.1177/2048872619828291
|View full text |Cite
|
Sign up to set email alerts
|

Acute diagonal-induced ST-elevation myocardial infarction and electrocardiogram-guidance in the era of primary coronary intervention: New insights into an old tool

Abstract: Background: Previous studies, published before the advent of primary reperfusion, described the electrocardiographic features of ST-segment elevation myocardial infarction (STEMI) caused by total diagonal artery occlusion, as demonstrated at pre-discharge coronary angiography. We aimed to assess the electrocardiographic and echocardiographic features in STEMI unequivocally attributed to a diagonal lesion in the era of primary coronary intervention. Methods: The electrocardiograms and echocardiograms of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Vessel size is the most commonly used parameter to define the clinical significance of a side branch. 13 Koo et al developed a new scoring system (SNuH score) that incorporated the number and distribution of branches as well as the size, to better reflect the myocardial mass at risk ([(Size (S), vessel diameter ≥2.5 mm; Number (Nu) number of diagonal branches ≤2; Highest (H), no branch below the target branch)]). They stated that SNuH score was higher in branches with ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vessel size is the most commonly used parameter to define the clinical significance of a side branch. 13 Koo et al developed a new scoring system (SNuH score) that incorporated the number and distribution of branches as well as the size, to better reflect the myocardial mass at risk ([(Size (S), vessel diameter ≥2.5 mm; Number (Nu) number of diagonal branches ≤2; Highest (H), no branch below the target branch)]). They stated that SNuH score was higher in branches with ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Fanne et al reported that more severe lateral lead ST-elevations were related to higher SNuH score and pre-intervention TIMI flow. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of D flow might be associated with poor prognosis of patents with STEMI. However, the clinical significance of the two occlusion scenarios is quite different, with the former being most common, of greater severity, and with worse prognosis [11,13,14], while isolated D occlusion is relatively rare and appears mainly inconsequential [15]. Therefore, distinction between the two scenarios is of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Fanne et al studied the ECG and echocardiographic findings of 123 STEMI patients that underwent coronary angiography in a retrospective series to determine whether the culprit vessel for primary PCI was the first diagonal or the proximal or mid LAD branch. 8 They reported that any degree of STE measured at the J-point + 40 ms localized to leads I, aVL, and V2, sparing leads V3–5, associated with reciprocal inferior ST segment depression was more likely to be associated with a proximal diagonal branch lesion compared with STE in leads V1 and V3–6, in which correlated with a proximal LAD lesion. The most common wall motion abnormalities associated with the first diagonal branch were localized to the apical-lateral, apical-anterior, and apical-inferolateral regions.…”
mentioning
confidence: 98%